Common Bean (Phaseolus vulgaris L.) Accumulates Most S-Methylcysteine as Its γ-Glutamyl Dipeptide - Saboori-Robat, Elham (Plants (Basel), 2019)
The common bean (Phaseolus vulgaris) constitutes an excellent source of vegetable dietary protein. However, there are sub-optimal levels of the essential amino acids, methionine and cysteine. On the other hand, P. vulgaris accumulates large amounts of the γ-glutamyl dipeptide of S-methylcysteine, and lower levels of free S-methylcysteine and S-methylhomoglutathione. Past results suggest two distinct metabolite pools. Free S-methylcysteine levels are high at the beginning of seed development and decline at mid-maturation, while there is a biphasic accumulation of γ-glutamyl-S-methylcysteine, at early cotyledon and maturation stages. A possible model involves the formation of S-methylcysteine by cysteine synthase from O-acetylserine and methanethiol, whereas the majority of γ-glutamyl-S-methylcysteine may arise from S-methylhomoglutathione. Metabolite profiling during development and in genotypes differing in total S-methylcysteine accumulation showed that γ-glutamyl-S-methylcysteine accounts for most of the total S-methylcysteine in mature seed. Profiling of transcripts for candidate biosynthetic genes indicated that BSAS4;1 expression is correlated with both the developmental timing and levels of free S-methylcysteine accumulated, while homoglutathione synthetase (hGS) expression was correlated with the levels of γ-glutamyl-S-methylcysteine. Analysis of S-methylated phytochelatins by liquid chromatography and high resolution tandem mass spectrometry revealed only small amounts of homophytochelatin-2 with a single S-methylcysteine. The mitochondrial localization of phytochelatin synthase 2—predominant in seed, determined by confocal microscopy of a fusion with the yellow fluorescent protein—and its spatial separation from S-methylhomoglutathione may explain the lack of significant accumulation of S-methylated phytochelatins.